Stevan Lilić, Administrative Law in Serbia, Belgrade: Faculty of Law, University of Belgrade, 2022, pp. 383 - Milenkovic, Marko (Review of European and Comparative Law, 2026)
A review of Stefan Lilić’ book titled "Administrative Law in Serbia" published by Faculty of Law, University of Belgrade